2005
DOI: 10.3171/spi.2005.3.2.0098
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive microendoscopy-assisted transforaminal lumbar interbody fusion with instrumentation

Abstract: The METLIF technique provided an option for percutaneous interbody fusion similar to that in open surgery while minimizing destruction to adjacent tissues. This technique was safe and exhibited a trend toward decreased intraoperative blood loss, postoperative pain, total narcotic use, and the risk of transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
187
3
7

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(208 citation statements)
references
References 26 publications
10
187
3
7
Order By: Relevance
“…When compared to the open-PLF group that required average incision of 12 cm, a statistically equivalent fusion rate (97%) was achieved in the MIS-PLF group (vs. 100% in the open-PLF group). Table 3 summarizes the surgical times and intraoperative blood loss of MIS-PLF and Open-PLF in this study with comparative data from previously published TLIF reports [2,3,6,[10][11][12][13]. In previous TLIF studies, the MIS procedure tended to take more surgical time than open TLIF [3,6,10,11,13]; however, some authors reported a shorter surgical time [2,12].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…When compared to the open-PLF group that required average incision of 12 cm, a statistically equivalent fusion rate (97%) was achieved in the MIS-PLF group (vs. 100% in the open-PLF group). Table 3 summarizes the surgical times and intraoperative blood loss of MIS-PLF and Open-PLF in this study with comparative data from previously published TLIF reports [2,3,6,[10][11][12][13]. In previous TLIF studies, the MIS procedure tended to take more surgical time than open TLIF [3,6,10,11,13]; however, some authors reported a shorter surgical time [2,12].…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, there have been several case series and comparative studies on minimally invasive lumbar spine fusions [1,[6][7][8][9][10][11][12][13][14]. In the present study, percutaneous pedicle screw-rod instrumentation was used for MIS-PLF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since then, the minimally invasive techniques have been upgraded and used more extensively in the clinical practice. Isaacs et al [8] analyzed the results of 20 patients treated with posterior percutaneous screw fixation and minimally invasive cage interbody fusion, with a significant reduction of intra-operative blood loss, postoperative blood transfusions, and average length hospital stay versus conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing technological progress led to the development of specific percutaneous surgical techniques to treat lumbar degenerative diseases [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%